Effect of amylose deposition on potato tuber starch granule architecture and dynamics as studied by lintnerization1. Issue 1 (23rd October 2012) - Wikman, Jeanette; Blennow, Andreas; Bertoft, Eric
Abstract The effect of amylose deposition on the amylopectin crystalline lamellar organization in potato starch granules was studied by mild acid, so‐called lintnerization, of potato tuber starch transgenically engineered to deposit different levels of amylose. The starch granules were subjected to lintnerization at different temperatures (25, 35, and 45°C) and to two levels of solubilization, ∼ 45 and 80%. The rate of the lintnerization increased with temperature but was suppressed by amylose. The molecular size of the lintner dextrins increased with temperature, but this effect was suppressed by the presence of amylose. At high temperatures and low‐amylose content, the degree of branches was high with the concomitant increase in size in the dextrins. A portion of the branches was resistant to debranching enzymes possibly due to specific structural formations. The effects of temperature suggested a unique granular architecture of potato starch, and a model showing the dependence of temperature on the dynamic arrangement of amylopectin and amylose in the crystalline and amorphous lamellae for the potato starch is suggested. © 2012 Wiley Periodicals, Inc.